Pengaruh pendidikan gizi dalam upaya meningkatkan kepatuhan konsumsi zat besi melalui kelas ibu hamil - Siti Sulastijah; Sumarni DW; Siti Helmyati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2015)
Background: Iron deficiency anemia contributed to a number of 50% in anemia and caused mortality of 841,000 every year in the world. Nutrition education before iron supplementation is needed because of low compliance in pregnant women. Gatak Sub District that is located in Sukoharjo Regency had the highest risk in pregnant women by 20.02%.Objective: This research aimed to know the effect of nutrition education in an effort to increase compliance of iron consumption through prenatal classes in Gatak Sub district Sukoharjo Regency.Method: The method of this research was quasi experiment with pre test-post test with non equivalent control group design. The samples of this research were 70 pregnant women who fulfilled inclusion and exclusion criteria. A number of 33 pregnant women were in treatment group and 37 pregnant women were in control group. Treatment group received a nutrition education through anemia booklet and iron supplementation which contained 60 mg sulfas ferosus and 400 µg folic acid on a daily basis in prenatal classes for 3 months. Control group did not receive a nutrition education, but still received a daily iron supplementation for 3 months. Independent t-test and paired t-test were used to analyze data.Results: The knowledge level (higher 12.59), compliance of iron consumption (15.16%), food intakes including energy (higher 9.24%), protein (higher 10.98%), and Fe (higher 6.68%), although those food intakes were still below the RDA, and hemoglobin level (higher 0.44 g/dl), in treatment group compared with control (p<0.05). The factors of age, education level, household expenditure, parity, ANC, nutritional status, and last birth spacing did not affect the compliance of iron consumption (p>0.05).Conclusion: The nutrition education affected the increase in compliance of iron consumption through prenatal classes in Gatak Sub District Sukoharjo Regency.